Should the marketing of subordinated debt be restricted/different in one way or the other? What to do in the case of mis-selling? - Martin R. Götz; Tobias Tröger (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
An important prerequisite for the efficiency of bail-in as a regulatory tool is that debt holders are able to bear the cost of a bail-in. Examining European banks' subordinated debt we caution that households may be investors in bail-in able bonds. Since households do not fulfil the aforementioned prerequisite, we argue that European bank supervisors need to ensure that banks' bail-in bonds are held by sophisticated investors. Existing EU market regulation insufficiently addresses mis-selling of bail-in instruments.
urn:nbn:de:hebis:30:3-395948
Keywords: 330; bail-in; BRRD; subordinated debt; EU market regulation